Estimation of Probabilities An essay on modern bayesian methods - Good, Irving John (Cambridge M I T Press, 1965)
The problem of how to estimate probabilities has interested philosophers, statisticians, actuaries, and mathematicians for a long time. It is currently of interest for automatic recognition, medical diagnosis, and artificial intelligence in general. The main purpose of this monograph is to review existing methods, especially those that are new or have not been written about in an organized way.
Keywords: Mathematics probabilities; Estimation of probabilities; Mathematics